(untitled) (Journal of the College of Basic Education, 2026)
Between 1917 and 1970, Iraq’s agricultural policy underwent major changes. During British rule, feudalism prevailed and land was controlled by a small elite. After the 1958 Revolution, agrarian reform aimed to redistribute land to peasants, reduce inequality, and strengthen the agricultural economy. However, the reform process faced major obstacles due to lack of technical support and infrastructure.